Sphingomyelinase activity promotes atrophy and attenuates force in human muscle fibres and is elevated in heart failure patients. Issue 5 (18th July 2022) - Olsson, Karl; Cheng, Arthur J.; Al‐Ameri, Mamdoh; Tardif, Nicolas; Melin, Michael; Rooyackers, Olav; Lanner, Johanna T.; Westerblad, Håkan; Gustafsson, Thomas; Bruton, Joseph D.; Rullman, Eric
Abstract: Background: Activation of sphingomyelinase (SMase) as a result of a general inflammatory response has been implicated as a mechanism underlying disease‐related loss of skeletal muscle mass and function in several clinical conditions including heart failure. Here, for the first time, we characterize the effects of SMase activity on human muscle fibre contractile function and assess skeletal muscle SMase activity in heart failure patients. Methods: The effects of SMase on force production and intracellular Ca 2+ handling were investigated in single intact human muscle fibres. Additional mechanistic studies were performed in single mouse toe muscle fibres. RNA sequencing was performed in human muscle bundles exposed to SMase. Intramuscular SMase activity was measured from heart failure patients ( n  = 61, age 69 ± 0.8 years, NYHA III‐IV, ejection fraction 25 ± 1.0%, peak VO2 14.4 ± 0.6 mL × kg × min) and healthy age‐matched control subjects ( n  = 10, age 71 ± 2.2 years, ejection fraction 60 ± 1.2%, peak VO2 25.8 ± 1.1 mL × kg × min). SMase activity was related to circulatory factors known to be associated with progression and disease severity in heart failure. Results: Sphingomyelinase reduced muscle fibre force production (−30%, P  < 0.05) by impairing sarcoplasmic reticulum (SR) Ca 2+ release ( P  < 0.05) and reducing myofibrillar Ca 2+ sensitivity. In human muscle bundles exposed to SMase, RNA sequencing analysis revealed 180 and 291 genes as up‐regulated and down‐regulated, respectively, at a FDR of 1%. Gene‐set enrichment analysis identified 'proteasome degradation' as an up‐regulated pathway (average fold‐change 1.1, P  = 0.008), while the pathway 'cytoplasmic ribosomal proteins' (average fold‐change 0.8, P  < 0.0001) and factors involving proliferation of muscle cells (average fold‐change 0.8, P  = 0.0002) where identified as down‐regulated. Intramuscular SMase activity was ~20% higher ( P  < 0.05) in human heart failure patients than in age‐matched healthy controls and was positively correlated with markers of disease severity and progression, and with several circulating inflammatory proteins, including TNF‐receptor 1 and 2. In a longitudinal cohort of heart failure patients ( n  = 6, mean follow‐up time 2.5 ± 0.2 years), SMase activity was demonstrated to increase by 30% ( P  < 0.05) with duration of disease. Conclusions: The present findings implicate activation of skeletal muscle SMase as a mechanism underlying human heart failure‐related loss of muscle mass and function. Moreover, our findings strengthen the idea that SMase activation may underpin disease‐related loss of muscle mass and function in other clinical conditions, acting as a common patophysiological mechanism for the myopathy often reported in diseases associated with a systemic inflammatory response.